Chronic sleep deprivation increase the risk of Alzheimer's disease - Szabat, Przemysław; Poleszak, Julita; Piwoński, Michał; Kozyra, Magdalena; Wiśniewski, Karol; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Introduction: Sleep deprivation is a common phenomenon among modern society. Due to the fact that many people are chronically sleepless, the possible negative consequences of sleep disorders for health should be investigated.The aim of the study: The aim of this article is to analyze the studies linking sleep disorders with changes in β-amyloid levels and the development of Alzheimer's disease.Material and method: Standard criteria were used to review the literature data. A search of articles in English was carried out in the PubMed and Google Scholar database.Description of the state of knowledge: The studies described show that sleep deprivation increases the level of βA in cerebrospinal fluid (CSF) in humans. This suggests that chronic sleep disturbances may contribute to the formation of amyloid plaques and other pathologies found in AD, which leads to an increased risk of this disease.Summary: The data confirms that sleep provides an important function in maintaining the metabolic homeostasis of neurons, and sleep deprivation significantly raises the level of βA in CSF. However, we still can not tell if a night with sufficiently long sleep can negate the accumulation of β-amyloid caused by poor nocturnal sleep, but this is undoubtedly the direction to be investigated in future years.